2000
DOI: 10.1038/sj.bmt.1702636
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of autoimmune hearing loss in MRL/lpr mice by bone marrow transplantation

Abstract: Summary:We examined the effects of bone marrow transplantation (BMT) on immune-mediated inner ear diseases in MRL/Mp-lpr/lpr (MRL/lpr) mice, which manifest not only lupus nephritis but also sensorineural hearing loss (SNHL) at the age of 20 weeks. These mice were treated with cyclophosphamide (CY) and irradiation (5 Gy × 2), followed by the transplantation of bones plus bone marrow cells from allogeneic normal C57BL/6 mice at the age of 12 weeks. Hematolymphoid cells were reconstituted with donor-derived cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…4 We have previously shown that autoimmune mechanisms participate in the development of the sensori-neural hearing loss in MRL/lpr mice. 12,13 We have also demonstrated that T cells in the systemic circulation infiltrate the inner ear and proliferate locally as a consequence of the immune response. 20 On the other hand, it has been shown that macrophages support the regeneration of the central and peripheral nervous system; 21,22 the cells secrete interleukin-1 (IL-1) 23 and mediate the release of nerve growth factor (NGF) in a variety of tissues, including Schwann cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…4 We have previously shown that autoimmune mechanisms participate in the development of the sensori-neural hearing loss in MRL/lpr mice. 12,13 We have also demonstrated that T cells in the systemic circulation infiltrate the inner ear and proliferate locally as a consequence of the immune response. 20 On the other hand, it has been shown that macrophages support the regeneration of the central and peripheral nervous system; 21,22 the cells secrete interleukin-1 (IL-1) 23 and mediate the release of nerve growth factor (NGF) in a variety of tissues, including Schwann cells.…”
Section: Discussionmentioning
confidence: 98%
“…12 We have also demonstrated that the hearing loss and cochlear pathology are derived from defects in the bone marrow cells; BMT can be used to prevent the development of the sensori-neural hearing loss. 13 If senescence is accelerated by the dysfunctions of immunocompetent cells, the normalization of the immune system by allogeneic BMT should prevent accelerated senescence. Therefore, we examine whether allogeneic BMT can prevent the accelerated impairment of both immune functions and hearing.…”
Section: Discussionmentioning
confidence: 99%
“…SHL and immune dysfunction. Several factors including inflammaging, immune dysfunction, oxidative stress, genetic abnormality, ototoxic drugs, and noise exposure lead to AHL as a consequence of deterioration in the SG, hair cells, and striavascularis of the cochlea [12]- [18].…”
Section: Prevention Of Age-related Shl By Immune Rejuvenationmentioning
confidence: 99%
“…We performed allogeneic bone marrow transplantation (BMT) in which MRL/lpr recipient mice received bone marrow cells from young C57BL/6 mice which are non-autoimmune prone and show slow manifestation of presbycusis [12,13]. The BMT procedures consist of systemic irradiation with 9-10 Gy to delete immunocompetent cells, including bone marrow cells, in recipients and then inoculating bone marrow cells from C57BL/6 donor mice.…”
Section: Treatment Of Autoimmune Shl With Allogeneic Bone Marrow Tranmentioning
confidence: 99%
“…Thus, cochlear function and pathology are affected by, or coordinated with, the systemic environment including the immune system. We have also studied preventive treatments for progressive bilateral SHL caused by disturbances in systemic immunity with autoimmune diseases or aging, but not caused by genetic abnormalities or acoustic trauma [11][12][13][14][15][16][17][18].…”
mentioning
confidence: 99%